The impact of investor protection law on corporate policy and performance: Evidence from the blue sky laws - Agrawal, Ashwini K. (Journal of Financial Economics, 2013)
Recent studies have debated the impact of investor protection law on corporate behavior and value. I exploit the staggered passage of state securities fraud statutes (“blue sky laws”) in the United States to estimate the causal effects of investor protection law on firm financing decisions and investment activity. The statutes induce firms to increase dividends, issue equity, and grow in size. The laws also facilitate improvements in operating performance and market valuations. Overall, the evidence is strongly supportive of theoretical models that predict investor protection law has a significant impact on corporate policy and performance.